Critism of Toxic Masculinity in The Power Of The Dog Movie Based on Social Context - Prayoga, Gogo (Profesional Muda Cendekia Publishing, 2023)
The mass media is often able to raise and reveal portraits of reality and gender realities that develop in society. Film is one of the mass media that usually uses discourses related to gender reality to be used as a medium to influence society and convey criticism of social practices within it. The Power Of The Dog movie seems to use the discourse of Toxic Masculinity which is used to convey criticism of masculinity in men. This study aims to find out and dismantle further texts regarding criticisms of toxic masculinity developed in the movie and their relationship to the current social context. This study uses a qualitative approach with critical discourse analysis by Norman Fairclough through its three-dimensional analysis stages. The results of this study indicate The Power Of The Dog movie has presented and developed criticism of various aspects, contexts and social phenomena regarding toxic masculinity. First, there are still many cases of gender-based violence in society. Second, the increasingly massive movements/actions to fight for gender equality in global society. Third, the dominance of the patriarchal system is still strong, which negatively shackles and harms society. Fourth, many people or communities are starting to realize the importance of understanding gender equality in the system of people’s lives. Fifth, the intuitive context related to the media economy (financial) and institutional characterizations in the movie, basically have represented what is called a typology of autocratic leadership. Keywords : Toxic Masculinity, Patriarchal Domination, Gender, Social Context